2007
DOI: 10.1002/iroh.200510921
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Composition of Trichoptera from Karst Habitats, Plitvice Lakes Region, Croatia

Abstract: Adult Trichoptera were observed at the Plitvice Lakes, Croatia during two years (2000 and 2001) using pyramid-type emergence traps. A total of 1350 individuals and 37 species were collected. Throughout the study, the emergence patterns showed only minor variations regarding differences in particular habitats. During 2000 most species emerged in June, and in 2001 in May. The complete emergence period is shown for all collected species and studied in detail for abundant species. Excluding Allogamus uncatus, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 29 publications
9
64
0
Order By: Relevance
“…Similar results were obtained for caddisfly assemblages in the same hydrosystem (i.e. upstream sites were dominated by shredders, and tufa barriers by collectors), due to the specificity of these habitats and available food resources (Previšić et al, 2007;Šemnički et al, 2012).…”
Section: Stonefly Assemblages and Relationships With Environmental Vasupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were obtained for caddisfly assemblages in the same hydrosystem (i.e. upstream sites were dominated by shredders, and tufa barriers by collectors), due to the specificity of these habitats and available food resources (Previšić et al, 2007;Šemnički et al, 2012).…”
Section: Stonefly Assemblages and Relationships With Environmental Vasupporting
confidence: 78%
“…Specific geology and hydrology of these habitats, including vast array of available microhabitats, resulted in high level of speciation and endemism, which is why karst habitats were recognized as biodiversity hotspots (Bonacci, 2009;Ivković and Plant, 2015;Previšić et al, 2014). Nevertheless, ecology of their biota, including stoneflies, is still highly understudied (Previšić et al, 2007;Ivković et al, 2012Ivković et al, , 2014Šemnički et al, 2012;Čmrlec et al, 2013;Vilenica et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this investigation was to define a macrozoobenthos based biotic index that would reflect water quality and specific structure of the macroinvertebrate community for Karst Rivers in Croatia. Fauna surveys confirmed that the macrozoobenthic community of those rivers is composed of some different taxa in comparison to continental rivers in Croatia, especially some endemic taxa whose indicator values are unknown (Previšić et al, 2007;Kučinić & Malicki, 2001;Žganec & Gottstein, 2009). Known physicochemical parameters show that the concentration of CO 2 is higher in the upstream parts of karst rivers due to permanent groundwater flow.…”
Section: Introductionmentioning
confidence: 94%
“…stoneflies (Popijač and Sivec, 2009), caddisflies (Previšić et al, 2007;Šemnički et al, 2012), blackflies (Ivković et al, 2013a), aquatic dance flies (Ivković et al, 2013b) and riffle beetles (Mičetić Stanković et al, 2015). However, the ecological preferences of mayfly assemblages in this region are still poorly known (e.g.…”
Section: Introductionmentioning
confidence: 99%